Signifikasi Imejan Dalam Cerita Rakyat Sudut Kosmologi Etnik Lun Bawang - Febbie, Ruth Katawan. (Universiti Malaysia Sarawak (UNIMAS), 2018)
Folktale is one of the important elements there is in a cultural aspect of a community. It is the main source of reference in order to understand their tradition and culture. Images used in these tales represents the symbols of beliefs in their culture. These images later become an inspiration for the arts product that we have today. This research is conducted based on a Lun Bawang’s tale of origin that encompasses the ethnic’s cosmic beliefs and to analyse how these images are used in the making of the community’s art product.